An analysis of some major antennas’ using frequency 750 MHz to 850 MHz - Shirvastava, Rajesh; Shrivastava, A K (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> An antenna is transducer, an impedance matching device, a radiator and a sensor of electromagnetic waves. It is essential device/element in all types of communication and radar systems. It can be considered as a source of electromagnetic wave. In this research paper an attempt has been made to study the characteristics of major antenna using frequency from 750MHz to 850MHz. In this experiment as well as research ATS-B Antenna system trainer is utilized. An antenna (or aerial) is an electrical device which converts electric power into radio waves, and vice versa. It is usually used with a radio transmitter or radio receivers. In transmission, a radio transmitter supplies an oscillating radio frequency electric current to the antenna’s terminals, and the antenna radiates the energy from the current as electromagnetic waves(radio waves). In receptions , an antenna intercepts some of the power of an electromagnetic wave in order to produce a tiny voltage as its terminals, that is applied to a receiver to be amplified. Typically an antenna consists of an arrangement of metallic conductors (elements), electrically connected to the receiver or transmitter. As oscillating current of electrons forced through the antenna by a transmitter will create an oscillating magnetic field around the antenna elements, while the change of the electrons also creates an oscillating electric field along the elements. Antenna can be broadly classified by the directions in which they radiate or receive electromagnetic radiation. They can be isotropic ,omni-directional or directional. An antenna is chosen for a particular application according to its main physical and electrical characteristics. Further an antenna must perform in a desired manner for the particular application. An antenna can be characterized by the following key factors , not all are applicable to all types of antenna. Main characteristics of an antenna are : radiation resistance, radiation pattern, the bandwidth etc. Further it has been found that graph of antenna polar plot which describes about antenna characteristics. Antenna are essential components of all equipment that uses radio. They are used in systems such as radio broadcasting, broadcast television, two-way radio, communication receivers, radar, cell phones, and satellite communication, as well as other devices such as garage door openers, wireless microphones, Bluetooth enabled devices, wireless computer networks, baby monitors, and RFID tags on merchandise. This paper introduces antenna theory and discusses various antenna types and applications. The basic equations and principles of antenna theory are presented. Five different types of antennas are introduced: dipoles and monopoles, loop antennas, microstrip antennas, helical antennas, and horn antennas.The characteristics of each type of antenna are given. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>